Population and reproductive parameters of the red-tailed catfish, Phractocephalus hemioliopterus (Pimelodidae: Siluriformes), from the Xingu River, Brazil - FREITAS, Tiago Magalhães da Silva (Universidade Federal do Pará, 2019)
A field study of the sex ratio, length-weight ratio, body size at first gonadal maturation, and the breeding season of the red-tailed catfish, Phractocephalus hemioliopterus, was carried out in the region of the middle Xingu River in the eastern Amazon basin. The fish were sampled quarterly from September 2012 to January 2014 using gillnets and long lines. The sex ratio was balanced, and while males and females were similar in standard length, the females were heavier than the males, on average. The males presented negative allometric growth, and the females, isometric growth. The estimated size at first maturity was 77.8 cm. The variation in the gonadosomatic index and the greater frequencies of mature specimens indicated a reproductive peak at the beginning of the high-water (flood) period. As P. hemioliopterus is an important commercial fish, our findings will contribute to the future development of effective conservation and management strategies, such as minimum catch size and a close season that is appropriate for the region. These data will also provide important insights for the evaluation of potential impacts on the biology of this fish resulting from the construction of Belo Monte dam.